Infinity reaper - Silvera, Adam, 1990- (Silvera, Adam, 1990- Infinity cycle, 2021)
"Emil and Brighton defied the odds. They beat the Blood Casters and escaped with their lives -- or so they thought. When Brighton drank the Reaper's Blood, he believed it would make him invincible, but instead the potion is killing him. In Emil's race to find an antidote that will not only save his brother but also rid him of his own unwanted phoenix powers, he will have to dig deep into the very past lives he's trying to outrun. Though he needs the help of the Spell Walkers now more than ever, their ranks are fracturing, with Maribelle's thirst for revenge sending her down a dangerous path. Meanwhile, Ness is being abused by Senator Iron for political gain, his rare shifting ability making him a dangerous weapon. As much as Ness longs to send Emil a signal, he knows the best way to keep Emil safe from his corrupt father is to keep him at a distance. The battle for peace is playing out like an intricate game of chess, and as the pieces on the board move into place, Emil starts to realize that he may have been competing against the wrong enemy all along."--